2021
DOI: 10.1016/j.heliyon.2021.e07938
|View full text |Cite
|
Sign up to set email alerts
|

Integration of host resistance, fungicides, and spray frequencies for managing Fusarium head blight of bread wheat under field conditions in southern Ethiopia

Abstract: A field experiment was carried out in Adiyo, Bonke, Chencha, Sodo zuriya, and North Ari districts, they are found in Southern Ethiopia, during the 2019 main production season. The objective of the experiment was to evaluate the effectiveness of the integrations of host resistance and application of fungicides with designated spray frequency on Fusarium head blight under natural epiphytotic conditions and to determine the management effects on yield and yield components of wheat. The treatments consisted of whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…During the study, FHB symptoms were first observed on Hidase, Kakaba, Danda'a, Kingbird, and Ogolcho genotypes at the Zadok's growth stage (ZGS) of 59 at Adiyo, Gedeb, North Ari, Sodo Zuriya, Hubareg, Chencha, and Bonke. FHB symptoms observed on the test wheat genotypes were in agreement with its typical symptoms reported by other scholars in different parts of the world (Gilbert and Tekauz 2000;Murray et al 2009; Dill-Macky Ghimire et al 2020;Mengesha et al 2021Mengesha et al , 2022. On the other hand, the identified Fusarium species such as F. graminearum, F. culmorum, F. avenaceum, F. poae, F. ussurianum, F. semitectum, F. lateritium, F. sambucinum, and F. heterosporum were in line with the reports of Earecho et al (2020), Getachew et al (2022), and Mengesha et al (2021 in Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…During the study, FHB symptoms were first observed on Hidase, Kakaba, Danda'a, Kingbird, and Ogolcho genotypes at the Zadok's growth stage (ZGS) of 59 at Adiyo, Gedeb, North Ari, Sodo Zuriya, Hubareg, Chencha, and Bonke. FHB symptoms observed on the test wheat genotypes were in agreement with its typical symptoms reported by other scholars in different parts of the world (Gilbert and Tekauz 2000;Murray et al 2009; Dill-Macky Ghimire et al 2020;Mengesha et al 2021Mengesha et al , 2022. On the other hand, the identified Fusarium species such as F. graminearum, F. culmorum, F. avenaceum, F. poae, F. ussurianum, F. semitectum, F. lateritium, F. sambucinum, and F. heterosporum were in line with the reports of Earecho et al (2020), Getachew et al (2022), and Mengesha et al (2021 in Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
“…This could be due to the variation in environmental conditions and the existence of various Fusarium species, which affect the interaction between FHB and wheat genotype for epidemic development. Variation in genotypic response to FHB has been known to result from variations in climate conditions and Fusarium species (Buerstmayr et al 2008;Beres et al 2018;Earecho et al 2020;Mengesha et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flusilazole and tebuconazole selected in this study have high antifungal activities against F. equiseti and F. acuminatum, which is consistent with the results of a previous study [48]. In addition, Mengesha et al [50] reported that tebuconazole is effective for controlling wheat scab; thus, triazole fungicides such as flusilazole and tebuconazole could be used to control leaf spot of R. glutinosa caused by Fusarium spp. In our study, prochloraz showed high antifungal activity against F. equiseti and F. acuminatum.…”
Section: Discussionsupporting
confidence: 90%